First occurrence of Melanoides tuberculata (O. F. Müller, 1774) in an open environment in the Czech Republic - Radovan Coufal; Luboš Beran (Malacologica Bohemoslovaca)
The invasive species Melanoides tuberculata (O. F. Müller, 1774) is reported from the open environment from the Czech Republic for the first time. An abundant population was found in the artificially heated Skryjský potok, a stream which flows from the cooling reservoir below the Dukovany nuclear power plant. The species is unlikely to occur outside the heated water due to its affinity for warm water.